An Alternative Method for the Gamma Function derived from Natural Logarithm and Pi Function - Chinnaraji Annamalai; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Several professors of mathematics from the renowned universities in Australia, Canada, Europe, India, USA, etc. argue with me that the gamma function was not derived from the factorial function. For them, this paper presents the derivation of gamma function from the natural logarithm and Euler’s factorial function. Also, a novel factorial theorem, which is alternative to the gamma function, is introduced in this article and it computes the accurate values of factorial for positive real numbers.